Pelatihan Memasarkan Produk Ke Media Sosial Untuk Pelaku Wirausaha Destinasi Wisata Danau Cipondoh - Heny Ratnanningtyas Heny; Reno Catelya Dira Oktavia; Anita Swantari; Florensia Herienda (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
This service aims to train product marketing on social media for food stall entrepreneurs in the Lake Cipondoh Destination. The method of implementing this activity is carried out by counseling and training using social media, namely Facebook and Instagram which includes several stages, namely: (1) The initial stage is preparing training facilities, training venues and training materials; (2) The stages of implementation are identifying the participants' social media knowledge, then providing counseling and training on marketing using social media; (3) The evaluation stage is to assess the ability of the trainees to use social media as a means of marketing their products. The results of this activity provide better benefits and results for food stall entrepreneurs, namely in the form of increasing recognition of the products offered and increased sales of these products, because they have marketed their products online and have wider access.